Analisis Manajemen Perubahan Berbasis Teknologi sebagai Inovasi Pedagogis dalam Sistem Pembelajaran di SDN Merjosari 3 Malang - Agus Saifur Rizal; Ramadhan Rivan Tavano; Syifa Ayu Fadillah; Ahmad Firdaus; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
The study aims to analyze the implementation of technology-based change management as a pedagogical innovation in the learning process at SDN Merjosari 3 Malang. The study’s background stems from developments in science and technology that require schools to adjust their teaching practices to become more effective, innovative, and relevant to 21st-century educational needs. The research used a qualitative approach with interviews, observations, and documentation involving educators directly engaged in implementing learning technologies. Findings indicate that technology was applied through the use of LCDs, Interactive Flat Panels (IFPs), digital learning platforms, Google Forms, and internet-based media in teaching and learning activities. The learning model, which previously relied heavily on lectures and textbooks, has shifted toward a more interactive, visual approach that fosters students’ critical thinking skills. The school also supported this change through teacher training, provision of technological facilities, and collaboration with parents and other stakeholders. Although challenges such as limited internet connectivity and power supply exist, the use of technology has been shown to help students grasp learning materials more quickly. Thus, technology-based change management successfully introduced pedagogical innovations that improved the effectiveness and quality of elementary-level learning.